Scoring ligand efficiency - Polanski, Jaroslaw; Duszklewicz, Roksana; Pedrys, Anna; Gasteiger, Johann (Acta Poloniae Pharmaceutica, 2019)
Ligand efficiency (LE) is a molecular descriptor that probes the ratio of potency vs. heavy atom count (HAC). As an estimator of drug candidates, LE emphasizes a low heavy atom count more than potency. The objective was to design a novel transform where potency and the HAC would be balanced more evenly. A series of novel descriptors SCORE were defined to evaluate the co-influence of potency and the HAC. In particular, the product ligand efficiency (PLE) was designed and tested using the data of the ChEMBL, PubChem as well as the selected series of drugs and drug-fragments.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Activity; ChEMBL; Drug design; Drugs; Ligand efficiency; Product ligand efficiency: heavy atom count; PubChem